Team dynamics at Suvasi Textiles - Sharda, Kirti (London : Indian Institute of Management, Ahmedabad, 2019)
The management team of Suvasi Textiles needs to decide whether to accept a new order or not. Accepting the order would enable the company to set out on a new path of growth, which was needed in the highly competitive textile market. There was a likelihood that the initial order, though small, would lead to larger orders. However, the risks were many. The new order required substantial capital outlay for procuring new machineries and technologies. The payment terms were not very favourable and asked for significant addition to working capital apart from taking on a credit risk. Limited operational capabilities of Suvasi Textiles meant that the firm would have to divert significant resources from existing production to fulfill this order. It was also probable that some employees would have to be laid off and newer people with more relevant skills would have to be hired. Any loss from this order could have a crippling effect on the stability of the firm and its survival. There were fears around destroying the legacy of the firm as well.
Originally Published InSharda, K. (2019). Team Dynamics at Suvasi Textiles. IIMA/OB0235. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Textile industry -- India -- Case studies; Industrial management -- India -- Case studies